Demograficzne i migracyjne uwarunkowania rozwoju oświaty w Zielonej Górze po połączeniu miasta Zielona Góra z gminą Zielona Góra = Demographic and migrational conditions of education development in Zielona Gora after joining the town of Zielona Gora and the commune of Zielona Gora - Osękowski, Czesław (1952- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
On 1 January 2015, the town of Zielona Gora and the commune of Zielona Gora merged to form a single territorial self-government. Before merging, the status of both local governments was as follows: the town of Zielona Gora was an urban commune with county rights; the commune of Zielona Gora was a rural commune, made up of 17 village administration offices, including 10 bordering with Zielona Gora.
Keywords: Zielona Góra; demografia; oświata; migracje; połączenie miasta z gminą; demography; education; migrations; the connection of city with community